Potential of Cashew Leaves (Anacardium occidentale L) for Health - Wijayanti, Willy; Horisanto, Abraham; Pamungkas, Ilham Wahyu; Jannah, Syerina Raihatul; Agustin, Venny (FoodTech: Jurnal Teknologi Pangan, 2024)
Traditionally employed in folk medicine, cashew leaf (Anacardium occidentale L.) has recently attracted a lot of scientific attention because of its possible health advantages. According to recent research, cashew leaves are abundant in bioactive substances such as terpenoids, flavonoids, and tannins that have a variety of pharmacological actions, such as anti-inflammatory, anti-cancer, antidiabetic, and antioxidant qualities. These bioactive chemicals work through a variety of molecular processes, including scavenging free radicals, modifying inflammatory pathways, and increasing the activity of antioxidant enzymes. Studies conducted both in vitro and in vivo have demonstrated the potential of cashew leaf extracts in the treatment of a number of chronic illnesses, such as diabetes mellitus and other degenerative conditions. Additionally, cashew leaves have encouraging opportunities as a natural source for the creation of medications and functional foods, including herbal remedies, dietary supplements, and natural cosmetics. More research is needed to find out if cashew leaf extracts are safe and effective over the long term and to figure out exactly how these bioactive chemicals work. In order to maximize the use of cashew leaves, future research should concentrate on identifying the main bioactive chemicals, improving extraction techniques, and creating appropriate formulations.